Educação inclusiva na formação de pedagogos: um estudo comparado entre instituições de educação superior públicas de Minas Gerais - Maria Aparecida Calixto Faria (2020)
The present study aimed at investigate how the teacher training has been offered to Inclusive Education in Pedagogy Courses of three public Higher Education Institutions (IFES) located in the State of Minas Gerais, Brazil, and proceed from that investigation to the analysis of the conceptions that transverse the pedagogical proposition of the teachers that work with that content to the development of the construction of knowledge by the pedagogues regarding the teaching-learning process of studies with deficiencies enrolled at the school. Thus, we sought to answer to the following research problem: How the public education institutions that train teacher for Elementary education meet in their pedagogical project, specifically in the matter grid, the current legislation about Inclusive education in the training process of Pedagogy Course? The methodology consisted of a literature review, documentary and field researches of qualitative approach. The gathering of empirical data was carried out by means of the application of a form and also with semi-structured interviews, whose analysis took into consideration the contributions of Bardin (2016) about content analysis. The theoretical framework included publications from 2000 to 2020, exploring the contributions of Kuhnen (2017), Kassar (2012), Bastos (2012), Plestch (2009), Nakayama (2007), Glat (2006), and Glat and Fernandes (2005) among others. The main results of the research revealed that, despite of the political pedagogical project and other documents of the institutions presenting prescriptions defined in the Brazilian law regarding Inclusive Education, some of them present a higher specificity in the form of propositions of classes offered for training in the field of Inclusive Education. In relation the teachers’ perception on the theme, it meets the findings of recent researches that emphasize the need of a deepening on the teachers’ training in order to promote inside the school the effective inclusion of students with deficiency, towards a qualitative educational process. Thus, we concluded that it is necessary a reformulation of educative projects and of the curricular syllabus of Pedagogy courses in order that the content of Inclusive Education be offered my means of interdisciplinary, transdisciplinary and transversal perspectives in the matters of the curricular grid and not only in the disciplines regarding the education of students with deficiency in Elementary Education